INTERNALISASI NILAI KEBAIKAN AGAMA LAIN MELALUI PENDIDIKAN AGAMA KATOLIK DI SEKOLAH MENURUT NOSTRA AETATE - Maria Afrianti Mada; Ola Rongan Wilhelmus (Bahasa Indonesia, 2023)
The Nostra Aetate document is a teaching of the Catholic Church which teaches that every religion has good values. In the document of Nostra Aetate Art. 2, the Church expresses it’s respect for other religions, and at the same time invites everyone to build a religious dialogue with fellow believers of other religions. It is because the Church views dialogue as a means that helps everyone to recognize and understand the values ​​of goodness in other religions and learn to respect the teachings of others religious faith. This study uses qualitative research methods with research respondents consisting of the teachers who are teaching Catholic Religion. The aims of this research are to explain the teaching of the Nostra Aetate document; to describe the view of the Nostra Aetate document on other religions; and to identify the internalization of the good values ​​of other religions through Catholic religious teachingh in schools. The results of the study showed that the respondents had known and understood the content of Nostra Aetate document. Based on the results of the study, the respondents also understood the views of the Nostra Aetate document on other religions. Furthermore, the respondents have also tried to internalize the good values ​​of other religions to students through Catholic religious teaching in the schools.